2004
DOI: 10.1093/ndt/gfh425
|View full text |Cite
|
Sign up to set email alerts
|

4-Heptanone is a metabolite of the plasticizer di(2-ethylhexyl) phthalate (DEHP) in haemodialysis patients

Abstract: Background. There is an ongoing discussion about the risks of di(2-ethylhexyl) phthalate (DEHP) exposure for the general population as well as for specific subgroups in various medical settings. Haemodialysis patients certainly belong to the group with the highest exposure taking into account the repeated treatments over a long period of time. Many studies have shown that DEHP metabolites are more active with regard to cellular responses than DEHP itself. Although 4-heptanone has been shown to be a DEHP metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 26 publications
(50 reference statements)
2
29
0
Order By: Relevance
“…After manual revision of the list one of the compounds (4-heptanone) has been excluded of the analysis. 4-heptanone is a major metabolite of di (2-ethylhexyl) phthalate (DEHP), a plasticizer used in polyvinyl chloride products, not associated with insulin resistance or liver metabolism [19]. It is incorporated in many medical devices like tubing, infusion sets, and storage bags for blood, parenteral nutrition and dialysis fluids.…”
Section: Resultsmentioning
confidence: 99%
“…After manual revision of the list one of the compounds (4-heptanone) has been excluded of the analysis. 4-heptanone is a major metabolite of di (2-ethylhexyl) phthalate (DEHP), a plasticizer used in polyvinyl chloride products, not associated with insulin resistance or liver metabolism [19]. It is incorporated in many medical devices like tubing, infusion sets, and storage bags for blood, parenteral nutrition and dialysis fluids.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 4-heptanone and 2-pentanone were significantly increased in iMN patients, which might indicate some relationship between oxidative stress and iMN. Since ketones were reported to be particularly abundant in human urine [22] , Wahl et al [23] have identified that 4-heptanone in urine is most probably of exogenous origin, which is supposed to be a product of β-oxidation of 2-ethylhexanoic acid, a metabolic product of the plasticizer di-(2-ethylhexyl)-phthalate. Previous studies confirmed that 4-heptanone was related to more specific stages of diabetic polyneuropathy [24] .…”
Section: Discussionmentioning
confidence: 99%
“…4-Heptanone has been described previously in the plasma of hemodialysis patients as a degradation product of diethylhexylphthalate. 38 In analogy to 4-heptanone, 4-heptanal and 2-heptanone preferentially or exclusively occurred in patients undergoing hemodialysis as well. 18 The question arises of why the analysis of exhaled VOCs has not been used as a clinical diagnostic tool thus far, although uremic fetor has long been believed to be characteristic of renal failure.…”
Section: In the Breathmentioning
confidence: 99%